Making an Arduino Uno R3 Trainer as A Learning Support Tool in The Electronics Study Program - Jati Sumarah; Ajeng Tiara Wulandari; Asni Tafrikhatin; Juri Benedi; Akrim Rakhmatika Pambudi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2024)
Microcontroller technology is increasingly developing, so studying it requires a real device. The learning process for microcontroller practice at the Piksi Ganesha Indonesia Polytechnic Campus does not yet have sufficient tools, especially for Arduino Uno practice. The research aims to create a tool or trainer about Arduino Uno so that it can be used to support microcontroller learning in the Electronics Engineering Study Program. The research method uses Research & Development with stages including potential and problems, information gathering, product design, design validation, design improvement, product testing, and product revision. The research results are an Arduino Uno trainer with three inputs and three outputs. It is hoped that users can more easily understand the basics of microcontrollers with the media created.